Experimental Investigation of Egg Shell Powder as Partial Replacement with Cement In Concrete - T. Shruthi, Hruthik Kondabathula, Bharath Kumar S, Chandana Ankhila, Yashwanth Y (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
With increasing industrialization, the industrial by products (wastes) are being accumulated to a large extent, leading to environmental and economic concerns related to their disposal (land filling). Egg shells are the biodegradable waste obtained from chick hatcheries, bakeries, fast food restaurants. Among other biodegradable wastes, this can damage the surroundings and thus leads to ecological issues/contamination which would need appropriate treatment. In the ever-soaring tasks to change waste to wealth, the efficiency of adopting eggshells to advantageous application constitutes a concept worth recognizing. It is systematically acknowledged that the egg shell chiefly consists of calcium compounds. It is estimated that roughly 90 million tons of hen egg are generated throughout the world every year. In India, 77.7 billion eggs are produced in the year 2010-2011.Cement is an energy extensive industrial commodity and leads to the emission of a vast amount of greenhouse gases. By reducing the demand of cement, natural reserves of limestone can be preserved, energy can be saved and pollution due to CO2 can be reduced. In this project, concrete will be casted for M30 grade and the partial replacement of cement with egg shells powder (ESP) in the range of 0%, 2.5%, 5%, 7.5%, 10% and 12.5% by weight of cement. The workability, compressive strength and tensile strength were conducted and results were analysed. Keywords: egg shell powder (ESP), workability, tensile strength and compressive strength.